(untitled) (Profetik: Jurnal Komunikasi, 2024)
Ahead of the 2024 election, social media offers ease of production and access to its information. On the other hand, it also encourages the spread of misinformation and disinformation and has the potential to influence democracy in Indonesia. This research aims to investigate misinformation and disinformation on social media and provide policy recommendations. The researchers analyzed mis/disinformation content from the turnbackhoax.id site from 18 July - 26 September 2023 by using qualitative content analysis methods to identify patterns of spreading misinformation and disinformation content on social media. Thisresearch identified the dominance of hoax and clickbait content types and personal and social content topics. There are similar patterns of mis/disinformation on every social media; its content is the result of digital reproduction from social media, online media, and microstock sites. The researchers provide content moderation policy recommendations using the reeve model of the regulatory pyramid, which consists of regulatory laws, standards, and co-regulation through independent institutions.